Behavioral risk factors and effects of lifestyle-modification on the metabolic syndrome in adults. A Brazilian community-based study - Burini, Roberto Carlos [UNESP]; Michelin, Edilaine [UNESP]; Burini, Franz Homero Paganini [UNESP]; Moreto, Fernando [UNESP]; McLellan, Kátia Cristina Portero [UNESP] (My University, 2012)
Metabolic syndrome (MetS) is a complex disorder with definition and prognostic significance still on dispute but representing a growing public health problem. In this chapter by adding personal data to the reviewed literature it is described that MetS is determined by aging, less education and lower income subjects characterized by their obesogenic-atherogenic diets and lower level of physical activity. Cross-sectional analysis showed MetS associated with overweight, insulin resistance, inflammation and pro-oxidative status. Lifestyle-changes interventions are clinically more effective than drugs. The effectiveness of the dietary changes is based on low-energy dense diets mainly providing high dietary fiber intake. Increased physical activity is more effective with aerobic exercises (and increased cardiorespiratory fitness) than strength exercises. The obtained beneficial effects seem independent of body weight loss. The combination of both exercises along with diet is recommended for restoring health in MetS patients mainly through body fat loss. Follow-up data showed MetS reversal higher than 10% with less than six months if used combined interventions.Metabolic syndrome (MetS) is a complex disorder with definition and prognostic significance still on dispute but representing a growing public health problem. In this chapter by adding personal data to the reviewed literature it is described that MetS is determined by aging, less education and lower income subjects characterized by their obesogenic-atherogenic diets and lower level of physical activity. Cross-sectional analysis showed MetS associated with overweight, insulin resistance, inflammation and pro-oxidative status. Lifestyle-changes interventions are clinically more effective than drugs. The effectiveness of the dietary changes is based on low-energy dense diets mainly providing high dietary fiber intake. Increased physical activity is more effective with aerobic exercises (and increased cardiorespiratory fitness) than strength exercises. The obtained beneficial effects seem independent of body weight loss. The combination of both exercises along with diet is recommended for restoring health in MetS patients mainly through body fat loss. Follow-up data showed MetS reversal higher than 10% with less than six months if used combined interventions. © 2012 by Nova Science Publishers, Inc. All rights reserved.